Os efeitos no condicionamento fisico dos praticantes de treinamento funcional de uma academia de Belém do Pará - GOMES, Bruce Monteiro Holanda (2022)
The aim of the study was to verify the effects of functional training on the physical conditioning of women who practice functional training. The sample consisted of 14 women with mean age ±28.35 years, mean height ±160.64 cm and mean ±67.85 in body mass. The power of lower limbs, agility and localized muscular endurance were evaluated through the following tests: horizontal jump, quadrant jump and abdominal test. After 8 weeks of intervention in the jump test where the pre-training mean was 133 cm and after 8 weeks it was 138.5 cm, the correlation was 0.866, in localized muscle resistance there were 16 repetitions before the intervention and after 21 the correlation coefficient was 0.847, indicating that there was an improvement with statistical significance in both tests. Regarding the quadrant test, the sample obtained an average of 53.5 hops per minute in the pre-training and in the post-training, it obtained an average of 60.5 hops per minute where the correlation coefficient was 0.497, showing that there was an improvement, but without significance. It was concluded that the functional training protocol used resulted in improvements in all tests performed, but more efficient in the tests of power of lower limbs and localized muscle resistance.